2014
DOI: 10.1128/jvi.01173-14
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus-Derived Endogenous Viral Elements in Two South American Rodent Genomes

Abstract: bWe describe endogenous viral elements (EVEs) derived from parvoviruses (family Parvoviridae) in the genomes of the longtailed chinchilla (Chinchilla lanigera) and the degu (Octodon degus). The novel EVEs include dependovirus-related elements and representatives of a clearly distinct parvovirus lineage that also has endogenous representatives in marsupial genomes. In the degu, one dependovirus-derived EVE was found to carry an intact reading frame and was differentially expressed in vivo, with increased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 19 publications
2
44
0
1
Order By: Relevance
“…In addition to the possibly endogenized PRSs identified in these 31 invertebrate species, PRSs were also identified in the genomes of 16 animal species for which potential parvovirus endogenization has been previously reported (including nine arthropods, six chordates and one platyhelminthes; Fig. 3)202131323334.…”
Section: Resultsmentioning
confidence: 90%
“…In addition to the possibly endogenized PRSs identified in these 31 invertebrate species, PRSs were also identified in the genomes of 16 animal species for which potential parvovirus endogenization has been previously reported (including nine arthropods, six chordates and one platyhelminthes; Fig. 3)202131323334.…”
Section: Resultsmentioning
confidence: 90%
“…Unlike AAV Rep and other EPVs containing intact ORFs encoding complete or nearly complete Rep proteins (e.g. the Odegus4 element in the genome of the degu [ Octodon degus ]) [13], the enREP-Myo9 sequence does not contain nuclear localization signals. We cloned and expressed the Odegus4 element, demonstrating that this transcript can express a protein (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…We compared the localization of enRep-Myo9 with another EPV-encoded Rep protein: Odegus4, encoded by a dependoparvoviruses-derived EPV in the degu genome. We previously reported that this EPV is specifically transcribed in degu liver [13]. The predicted gene product contains at least two NLS, as it is expected for Rep proteins (which must locate to the nucleus to allow replication of parvoviral DNA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences derived from parvoviruses occur relatively frequently in animal genomes (13, 14, 17, 25, 26). However, these sequences overwhelmingly derive from a small proportion of parvovirus lineages.…”
Section: Discussionmentioning
confidence: 99%